Pengaruh Corporate Social Responsibility, Gross Profit Margin, Struktur Modal Dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019 - Nadia Z. Sitepu; Christine Ullysia Sinaga; Regina Aprilia Bancin; Mesrawati Mesrawati (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Indicators The Company's value may reflect the current state of the company from the expected future earnings. The purpose of the researchis to analyze whether Corporate Social Responsibility, Gross Profit Margin, Capital Structure and Financial Performance have an effect on the company's value indicators for manufacturing companies during 2017- 2019 listed in B EI. The samples are manufacturing companies listed on the Idx for 3 consecutive years, namely 2017-2019 which amounted to 95 companies with predetermined criteria. To complete this research, we use an application SPSS to view the final results. From the research that we have done,it can be seen the results of the test where Corporate Social Responsibility has no influence on the Company's Value, Gross Profit Margin influenceson the Value of the Company, The Capital Structure has no influence on the Company's Value and Financial Performance that has an influence on the Company's Value. Keywords: Corporate Social Responsibility, Gross Profit Margin, Capital Structure, Finacial Performance,Companies Value